COMMUNITY INTENTION IN THE WHISTLE-BLOWING SYSTEM DEVELOPMENT FOR SMOKE-FREE ZONES' LAW ENFORCEMENT IN KENDARI CITY, SULAWESI TENGGARA PROVINCE, INDONESIA - La Ode Hasnuddin S. Sagala; La Ode Ahmad Saktiansyah; Abdillah Ahsan (Public Health of Indonesia)
Background: Kendari City has set regional regulation No. 16 of 2014 about smoke-free zones (SFZs), however, it has been no tool that is optimal in law enforcement on the application of SFZs regulation in this region.